Model Pelanggaran dalam Pelaksanaan Pemilihan Kepala Daerah Kabupaten Pelalawan Berdasarkan Undang-Undang Pemilihan Kepala Daerah Tahun 2020 - Adrian Faridhi; Alexsander Yandra; Sudi Fahmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Election violations in the Pelalawan Regency Head Election will be used as evaluation material in the implementation of the next general election, the findings of violations provide a model/form for improvement. This study uses a normative legal research method that uses a statutory approach. The findings of this study are a model of election violations in the form of election criminal violations, election administrative violations, ethical violations and other legal violations, this is based on findings and reports examined by Bawaslu and by Gakumdu.